2022
DOI: 10.3390/cancers15010184
|View full text |Cite
|
Sign up to set email alerts
|

Long Non-Coding RNAs as Epigenetic Regulators of Immune Checkpoints in Cancer Immunity

Abstract: In recent years, cancer treatment has undergone significant changes, predominantly in the shift towards immunotherapeutic strategies using immune checkpoint inhibitors. Despite the clinical efficacy of many of these inhibitors, the overall response rate remains modest, and immunotherapies for many cancers have proved ineffective, highlighting the importance of knowing the tumor microenvironment and heterogeneity of each malignancy in patients. Long non-coding RNAs (lncRNAs) have attracted increasing attention … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 173 publications
0
3
0
Order By: Relevance
“…There are many kinds of ncRNAs, which can be roughly divided into two categories: (1) sncRNAs, shorter than 200 nucleotides, including microRNAs (miRNAs), PIWI-interacting RNAs (piRNAs), transport RNAs (tRNAs), ribosomal RNAs (rRNAs), small nuclear RNAs (snRNAs), small nucleolar RNAs (snoRNAs), and small interfering RNAs (small interfering RNAs). ( 2) lncRNAs refers to long noncoding RNAs, usually longer than 200 nucleotides (Bouyahya et al, 2022;Saadi et al, 2022).…”
Section: Non-coding Rnamentioning
confidence: 99%
“…There are many kinds of ncRNAs, which can be roughly divided into two categories: (1) sncRNAs, shorter than 200 nucleotides, including microRNAs (miRNAs), PIWI-interacting RNAs (piRNAs), transport RNAs (tRNAs), ribosomal RNAs (rRNAs), small nuclear RNAs (snRNAs), small nucleolar RNAs (snoRNAs), and small interfering RNAs (small interfering RNAs). ( 2) lncRNAs refers to long noncoding RNAs, usually longer than 200 nucleotides (Bouyahya et al, 2022;Saadi et al, 2022).…”
Section: Non-coding Rnamentioning
confidence: 99%
“…This same signaling initiates a regulatory mechanism to prevent overactivation of the immune system, in which the expression of immune checkpoint (IC) molecules 2 of 18 such as cytotoxic T lymphocyte-associated antigen-4 (CTLA-4; CD152) is upregulated on the lymphocyte cell membrane after T cell activation to compete for the same ligands as CD28, avoiding T cell overactivation and hyperactivity. Similarly, programmed cell death protein 1 (PD-1; CD279) and its ligands PD-L1 (PD-1 ligand 1; CD274; B7-H1) and PD-L2 (CD273; B7-DC); or B7-H3 (CD276) and its ligandstriggering receptor expressed on myeloid cell (TREM)-like transcript 2 (TLT-2), toll-like receptor 2 (TLR2) or interleukin-20 receptor subunit alpha (IL20RA), that inhibit T cell effector functions and induce T cell apoptotic death [2][3][4][5][6]. Another IC is the cluster of differentiation 47 (CD47), which binds to signal regulatory protein alpha (SIRPα) of membrane macrophages to inhibit tumor cell phagocytosis [7].…”
Section: Introductionmentioning
confidence: 99%
“…Among them, we can find: (1) small non-coding RNAs (sncRNAs), with less than 200 nucleotides, which include microRNAs (miRNAs), a class of highly conserved endogenous ncRNAs with approximately 22 nucleotides in length; and (2) long non-codingRNAs (lncRNAs) with a length above 200 nucleotides [1]. Various studies have reported the role of these ncRNAs as modulators of ICs molecules in the setting of human cancer [5,[18][19][20] and even the relationship between them to regulate the response to immunotherapy, given that, for example, lncRNAs can act as competitive endogenous RNAs (ceRNAs) of miRNAs, establishing an lncRNA-miRNA-mRNA regulation axis [21].…”
Section: Introductionmentioning
confidence: 99%